Breast MRI Interpretation Text and Online Case Analysis for Screening and Diagnosis. - Newstead, Gillian (Thieme Medical Publishers, Incorporated, 2020)
State-of-the-art resource details effective breast MRI techniques for improved screening and diagnosis Magnetic resonance imaging (MRI) of the breast has evolved into an important breast cancer screening tool and major advance in women's health. Breast MRI is currently the most sensitive detection technique for both non-invasive and invasive cancers and follow-up in women with a new breast cancer diagnosis. It is increasingly becoming the go-to imaging method for screening women at high and intermediate risk of breast cancer and those with dense breast tissue on mammography. Yet despite its re.